KONSEP PENDIDIKAN MULTIKULTURAL DI LEMBAGA PENDIDIKAN MUHAMMADIYAH (Studi Pemikran Prof. Dr. Abdul Mu’ti, M.Ed.) - Imam Taofik; Abdul Basit (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2022)
This research focuses on "MULTICULTURAL EDUCATION CONCEPT IN MUHAMMADIYAH EDUCATIONAL INSTITUTIONS (Prof. Dr. Abdul Mu'ti, M.Ed.) Thought Studies", literature review. The aim is to find out and examine how Prof. Dr. Abdul Mu'ti, M.Ed.The benefits obtained from the results of this research are that, for the author, it can be used as material for scientific studies in order to increase insight and analytical skills on problems that are directly related to the scientific field that the author is engaged in in college. Then, for educational institutions, it can be used as a vehicle for the development of knowledge according to the mission it carries, as well as an effort to increase its role in the field of community service. Moreover, for the community, it can be used as reference material and useful information for improving the quality of human resources through increasing the development of children according to the demands of Islamic teachings in the context of full human development in the current multicultural era, and the development of a whole society that is physically and mentally prosperous. safe and happy world hereafter. The method used in this research is to use the library research method, or what is called literature study is a method that the author uses to explore various library materials that have to do with the subject of study in writing this thesis.From the results of this study, it was concluded that the main research findings of Prof. Dr. Abdul Mu'ti, M.Ed stated in the Muhammadiyah Christian Book there were several points of thought that Prof. Dr. Abdul Mu'ti, M.Ed. present among others that Muhammadiyah is present as a movement that welcomes religious plurality, in the opinion of Prof. Dr. Abdul Mu'ti, M.Ed Muhammadiyah, despite its pure and modernist Islamic status, is able to answer the challenges of the times even in areas where the majority are non-Muslims. According to Prof.Dr. Abdul Mu'ti, M.Ed Muhammadiyah accepted social institutions from the West and adopted the Western education system. If this attitude continues to be carried out, it will strengthen optimism about the future of religious pluralism in Indonesia and focus on being a central role in building a strong national character, open to differences, and strong Indonesian integrity as well as educational progress, especially in Muhammadiyah educational institutions. This finding is certainly a reference for Muhammadiyah schools, especially those in Muslim-majority circles, which should be more advanced and developed when referring to the research findings of Prof. Dr. Abdul Mu'ti, M.Ed. so that there are no more cases of closing Muhammadiyah schools due to the absence of students such as the example in SMA Muhammadiyah Ciampea Bogor, Muhammadiyah schools need to be more welcome from any aspect that is positive and adopting the system or following the times as well as strengthening cultural propaganda.Keywords: Concept, Multicultural, Muhammadiyah